First-trimester abortion complicated with placenta accreta: A systematic review - Yeou-Lih Wang; Shih-Shien Weng; Wen-Chu Huang (Elsevier, 2019)
Placenta accreta is a potentially life-threatening condition that may complicate a first-trimester abortion in rare occasions, and it can be difficult to recognize. We reviewed the literature in PubMed-indexed English journals through August 2018 for first-trimester postabortal placenta accreta, after which 19 articles and 23 case reports were included. The risk factors for the development of abnormal placentation are previous cesarean section (87%), previous history of uterine curettage (43.5%), and previous history of surgical evacuation of a retained placenta (4.3%). Ten patients (43.5%) had an advanced age (≧35 years). Most patients clinically presented with vaginal bleeding, ranging from intermittent or irregular bleeding, persistent bleeding, and profuse or massive bleeding. The onset of symptoms might be during the intra- or immediate postoperative period. Some patients had delayed symptoms 1 week to 2 years postoperatively. Conservative management may be attempted as the primary rescue, including uterine artery embolization (UAE), transcatheter arterial chemoembolization (TACE) with dactinomycin, and laparoscopic hysterotomy with placental tissue removal. However, most reports in the literature suggested either abdominal or laparoscopic hysterectomy as the definitive treatment for first-trimester postabortal placenta accreta. High index of clinical suspicion with anticipation of placenta accreta in early pregnancy is highly essential for timely diagnosis, providing the physician better opportunities to promptly manage this emergent condition and improve outcomes. Keywords: First-trimester abortion, First-trimester pregnancy, Placenta accreta